2013
DOI: 10.1097/sih.0b013e318290a022
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Assessment for Evaluation of Team Skills

Abstract: The SAFE-TeamS was sensitive to individual differences and team skill training, providing evidence for validity. It is not clear whether different scenarios measure different skills and whether the scenarios cover the necessary breadth of skills. Use of multiple scenarios will support assessment across a broader range of skills. Future research is required to determine whether assessments using SAFE-TeamS will translate to performance in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
0
10
0
3
Order By: Relevance
“…Another study found positive correlations for students' written and OSCE scores between the final year of the dental curriculum and the results of the National Dental Examining Board (NDEB) of Canada examination. 20,21 In our study, although there were commonalities among all three assessments, there were also distinct areas of no overlap. However, other studies with medical and allied health care professionals found disparities between academic achievement and performance in clinical settings.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Another study found positive correlations for students' written and OSCE scores between the final year of the dental curriculum and the results of the National Dental Examining Board (NDEB) of Canada examination. 20,21 In our study, although there were commonalities among all three assessments, there were also distinct areas of no overlap. However, other studies with medical and allied health care professionals found disparities between academic achievement and performance in clinical settings.…”
Section: Discussionmentioning
confidence: 43%
“…18 However, each method is aimed at assessing different learning outcomes and serves to enhance the external validity of the assessments. 20,21 In our study, although there were commonalities among all three assessments, there were also distinct areas of no overlap. Furthermore, each of the three assessments was mapped against different learning outcomes for dentists as outlined by the General Dental Council.…”
Section: Discussionmentioning
confidence: 43%
“…Fifteen tools met initial inclusion criteria after the initial stage (TABLE 1). [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] After the second stage of review for adaptability of the tool, 5 tools remained. A total of 157 items were extracted and reduced to 81 discrete items for rating by Delphi panelists (FIGURE).…”
Section: Resultsmentioning
confidence: 99%
“…In my own research with colleagues, we found that two raters and eight or more scenarios were needed to attain high levels of relative reliability in scoring key teamwork skills. 11 For high-stakes assessment, scenario design supporting multiple, shorter evaluations may be more effective than fewer, longer scenarios which may be more typical of formative assessment simulation scenarios. 11 The scenarios evaluated by Everett et al in this issue of the Journal were adapted from scenarios used in the context of formative assessment for MEPA training.…”
mentioning
confidence: 99%
“…11 For high-stakes assessment, scenario design supporting multiple, shorter evaluations may be more effective than fewer, longer scenarios which may be more typical of formative assessment simulation scenarios. 11 The scenarios evaluated by Everett et al in this issue of the Journal were adapted from scenarios used in the context of formative assessment for MEPA training. 7 They were scripted, pre-programmed, and actors gave timed prompts.…”
mentioning
confidence: 99%